Association between Platelet and Iron Parameters in Patients with Iron Deficiency Anemia - Aftab Rabbani, Saqib Allah Dad, Ahsan Ayub, Bushra Adeel, Muhammad Azam, Ayesha Masood (Pakistan Journal of Medical & Health Sciences, 2022)
Iron deficiency anemia is the most prevalent anemia type and is identified by the use of blood tests for iron levels. In iron deficiency anemia, reactive thrombocytosis is a common complication. The study’s primary goal is to determine if there is a relationship between platelet and iron parameters in patients with iron deficient anemia. Place and Duration: This cross-sectional research was done among patients with iron deficiency anemia in the Department of Medicine and Pathology, Sharif Medical College, Lahore for one-year duration from January 2021 to December 2021. Method: This Observational research was conducted in the Department of Medicine and Pathology order to collect information. The platelet and iron parameters of 70 iron deficiency anemia patients were determined using blood samples taken from the patients. The data was analyzed with the help of SPSS version 20. Results: Patients with iron deficiency anemia were found to have thrombocytosis in 58 (82.9 percent) of the cases. When serum iron, percentage saturation, and platelet distribution were taken into consideration (all p0.001), platelet count was shown to be adversely connected to these variables, but a positive association was found between plateletcrit and platelet count (all p<0.05). There was a negative link between serum iron and plateletcrit (p<0.001) and PDW (p<0.05), but only a positive relationship was found with TIBC, mean platelet volume (p<0.05), and platelet (all p<0.05). There was a significant negative relationship between platelet count and mean platelet volume (p<0.001). Platelet and mean platelet volume correlated positively (p<0.05), while plateletcrit and mean platelet volume correlated negatively (p<0.05). Neither a correlation nor a non-correlation between iron parameters and mean platelet volume were discovered (p>0.05). Conclusion: When it comes to patients with iron deficient anemia, thrombocytosis is more prevalent than thrombocytopenia. The most critical factors impacting platelet count are serum iron and percentage saturation.